2017
DOI: 10.1016/j.tjog.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Ex utero intrapartum treatment for extremely low birth-weight neonates requiring resuscitation at birth

Abstract: When cesarean delivery is indicated in ELBW infants and intubation after birth is anticipated, DCC after establishing a secured airway may help maintain neonatal cardiovascular stability and allow physicians to resolve the technical difficulties of intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The 18 studies were published in journal issues between 2014 and 2023. However, some papers appeared online before their formal publication date, and that is how we included them in our review up to 14 November 2022 12–14,19–33 . We searched for all papers published since the inception of the databases we used, but the two earliest articles identified in this scoping review were published in 2014.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 studies were published in journal issues between 2014 and 2023. However, some papers appeared online before their formal publication date, and that is how we included them in our review up to 14 November 2022 12–14,19–33 . We searched for all papers published since the inception of the databases we used, but the two earliest articles identified in this scoping review were published in 2014.…”
Section: Resultsmentioning
confidence: 99%
“…We found that 164 neonates in five studies were stabilised or resuscitated on commercially available Lifestart trolleys (Inspiration Healthcare), 19,21,24,27,33 while 134 neonates in seven studies were placed on bedding, such as mattresses, drapes or towels 13,14,20,22,26,30,31 . Five papers reported that they used locally developed and assembled trolleys for a total of 88 neonates 23,25,28,29,32 . The commercial Concord trolley (Concord Neonatal B.V.) was used for nine neonates in one study 12 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Subramanian et al 12 cites one case in which the procedure had to be abandoned due to haemorrhage despite the use of harmonic scalpel; however, this was not an outcome in any of the cases reviewed. Hung et al 16 describes the placement of transarterial balloons bilaterally in the patient's internal iliac arteries as a preventative measure for postpartum haemorrhage. This is not described in any other cases and was not required to be used; therefore, may be an unnecessary invasive procedure.…”
Section: The Proceduresmentioning
confidence: 99%
“…Hung et al 16 explain that neonates with extremely low birth weight are very difficult to intubate and quickly deteriorate when attempts fail. They described EXIT procedures in two patients, one with a single fetus and one with twins, who were likely to have preterm labour.…”
Section: Extremely Low Birth Weightmentioning
confidence: 99%
See 1 more Smart Citation